SANCIONAR CON PENA PRIVATIVA DE LA LIBERTAD A LAS CONTRAVENCIONES TRIBUTARIAS - Pozo Salcedo, Fabricio Estuardo (2016)
En our tax legal system, the constituent Assembly has provided for powers to impose penalties, according to which the own tax administration can impose certain sanctions on offending taxpayers. The legal nature of administrative offences is, until now, because of a wide discussion, holding the independence of tax infringement of the criminal offence, trying to differentiate them from the conceptualization of both punitive regimes, arriving to settle to the protected object of administrative offences, which include tax offences, is not represented by the people or their rights, but by the action of the State in the entire field of the Publican. El right sanctioning tax administration, it is criminal in nature however, these 'sanctions' are distinguished from the "Peñas" themselves by an important issue of how to take into account that the authority that imposed those sanctions is public administration. This thesis refers to "Punish with penalty custodial of the freedom to the Contraventions tax"; where I believe that the procedure being applied to prosecute the taxpayer who does not comply with formal obligations with the public administration is not correct, because it allows the breakdown of the legal order established by the State by allowing you to avoid the determination of tax obligation. 6 At present the Ecuadorian tax code sets for these wrongful acts, pecuniary penalty not less than $30 and not more than 1500 United States dollars; without taking into account actions or omissions intentional or negligent, gravity and proportionality of damage caused, the principles of typicality and proportionality between the antijuridico, Act and the penalty established to sanction this, as well as the principle of guilt and recidivism as mitigating circumstances so that you can set penalties effective and useful. Against this tax problem, theoretical and empirical collection allowed to secure more accurately the research subject matter of this thesis, about the need for aggravated sanctions imposed on those who violate the tax law to evade the determination of their tax liabilities tax with deprivation of liberty, the purpose is to find the best way to ensure the fulfillment of the formal by the taxpayer or public official duties , and commitment to every citizen not only with the State but with peers, this consequently will contribute to the economic and social development of our country. Through field research failed to verify that there is a large number of contributors, ones that are unaware of tax legislation and others seeking knowledge how to evade it, causing serious damage to the National Treasury; from there the need to institute a reform body criminal tributary where to punish contraventions deemed the actions or omissions of the taxpayer or official to failure to comply with formal in a repetitive and intentional or negligent way duties and fulfilling the tax principles, punish with imprisonment of freedom, these antijuricos acts.